Verificação à fadiga de vigas de pontes de concreto armado: estudo comparativo entre o uso do trem-tipo normativo e as cargas reais nas rodovias brasileiras - Mascarenhas, Fernando Júnior Resende (2019)
Bridges and viaducts are important in the social and economic dynamics of a nation, and they are very important elements in transportation systems. In Brazil, freight transportation is predominantly by road. Therefore, viaducts and bridges are directly affected by the predominance of the road matrix. In recent years there has been an increase in the flow and weight of vehicles commuting on highways, which requires special attention to the structural performance of bridges and viaducts. Among the several structural problems to which these structures are susceptible, the longitudinal reinforcement fatigue deserves attention, especially in view of the increasing number of heavy vehicles. In spite of the heterogeneity of the real vehicles that travel in bridges and viaducts, the different national and international standards of mobile loads for bridges and road viaducts have their respective load trains for the dimensioning of such structures. The Brazilian Standard, NBR 7188:2013, has the TB 450 as its load train whose configuration represents a type vehicle of 450 kN. Based on that, this dissertation aims to analyze the fatigue in concrete and longitudinal reinforcement of beams of theoretical models of reinforced concrete bridges consisting of two, three and five beams. This estimate is made by considering the actual number of heavy vehicles from 2 to 6 axes of road stretches in the state of São Paulo over 9 years of data. Thus, the objective is to estimate the accumulated damage due to fatigue in concrete and longitudinal reinforcement; estimate the fatigue life of concrete and longitudinal reinforcement of bridge beams with different lengths; evaluate the deleterious impacts of fatigue on the different bridge lengths and built with two, three and five beams; to evaluate whether two-girder reinforced concrete bridges are recommended for design on high-traffic highways and to analyze whether the fatigue check indicated by the Brazilian standard using the Brazilian standard train is capable of representing the flow of real heavy vehicles. The methodology of this research is based on literature review about the phenomenon of fatigue and the necessary calculation procedures. These calculations will be performed using analytical methods and the use of Ftool to determine bending moments due to permanent and mobile loads in the span of the beams analyzed. For the calculation and verification of fatigue, theoretical bridge models with two, three and five beams with spans L of 10, 15 and 20 meters (m). In addition, two calculation scenarios are considered, where in Scenario 1 only the loads of 2 to 6 axle real vehicles are considered; and in Scenario 2, in addition to the actual vehicle loads, the 5 kN/m2 distributed load representing vehicles that can travel on the back and front of the analyzed vehicles is considered. Based on this, at the end of this project the following conclusions were found. The fatigue damage values calculated for the concrete were small and, thus they were considered negligible in all models analyzed in both Scenarios 1 and 2. As described in other studies found in the literature, the deleterious effects of fatigue are more noticeable in the longitudinal reinforcement than in the concrete itself. Thus, the fatigue life found for the longitudinal reinforcement deserves attention because in some cases it is less than the average design time of 75 years. In addition to this, the increasing of the gap makes the bridges have longer fatigue life. In addition, 5-beam bridges proved to be the longest in life, and 2-beam bridges are not recommended for locations with heavy truck traffic. Finally, it was found that the Brazilian normative type train is able to represent the current traffic of heavy vehicles.